Atomic-scale imaging of the ferrimagnetic/diamagnetic interface in Au-Fe3O4 nanodimers and correlated exchange-bias origin. Issue 45 (14th November 2018) - Zhu, Liu; Deng, Xia; Hu, Yang; Liu, Jian; Ma, Hongbin; Zhang, Junli; Fu, Jiecai; He, Suisui; Wang, Jun; Wang, Baodui; Xue, Desheng; Peng, Yong
Abstract : Magnetic phase transition was atomically imaged to govern the exchange bias effect in dumbbell-like ferrimagnetic/diamagnetic coupled Au/Fe3 O4 nanodimers. Abstract : Exchange-biased magnetic heterostructures have become one of the research frontiers due to their significance in enriching the fundamental knowledge in nanomagnetics and promising diverse applications in the information industry. However, the physical origin of their exchange bias effect is still controversial. A key reason for this is the lack of unequivocal observations of interface growth. In this work, we fill this gap by experimentally imaging the ferrimagnetic/diamagnetic interfaces of Au-Fe3 O4 nanodimers at the atomic level. A different physical mechanism from the reported mechanisms is found based on the atomic-resolution observation of their interfacial structure and electronic states, which reveals that the antiferromagnetic and ferromagnetic interactions of the formed weak/strong ferrimagnetic bilayer are responsible for the intrinsic exchange-bias origin in Au-Fe3 O4 nanodimers. The theoretical quantitative analysis of the exchange bias shift based on the observed interfacial occupation model agrees well with the experimental value for the exchange bias effect, strongly verifying the proposed exchange-bias mechanism.